1987
DOI: 10.1016/s0022-3476(87)80066-5
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia in pediatric outpatients: Cause and clinical manifestations

Abstract: The cause and clinical manifestations of pneumonia were studied in 98 pediatric outpatients. A viral diagnosis was established in 38 (39%) of the 98 patients, and a bacterial diagnosis in 19 (19%). Ten (53%) of the 19 patients with bacterial pneumonia had a concurrent viral infection. No clinical, laboratory, or radiographic findings that would reliably differentiate viral from bacterial infection were identified. This study suggests that bacterial pneumonia is more common in pediatric outpatients than previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
1
10

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(67 citation statements)
references
References 21 publications
2
54
1
10
Order By: Relevance
“…These results may corroborate previously reported etiological rates; in previous studies, the rate has been reported as 43% to 85% (14)(15)(16)(17)(18)(19)(20).…”
Section: Resultssupporting
confidence: 93%
“…These results may corroborate previously reported etiological rates; in previous studies, the rate has been reported as 43% to 85% (14)(15)(16)(17)(18)(19)(20).…”
Section: Resultssupporting
confidence: 93%
“…The frequency of claims was converted into a frequency of pneumonia episodes using the average number of medical visits (n=2.2) recorded in our retrospective study of cases of pneumonia in children younger than 10 years of age in Quebec and Manitoba (from the microcosting study of otitis and pneumonia described later). The proportion of pneumonia attributable to S pneumoniae was set at 22% based on values found in published studies (9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that bacterial pneumonia cannot be differentiated from viral pneumonia on the basis of a patient's characteristics, routine laboratory tests, or chest radiographic findings (32,33). White blood cell count or serum CRP levels sometimes help to differentiate between bacterial or viral infection (1,3).…”
Section: Discussionmentioning
confidence: 99%